Implementation of Guided Inquiry in Science Education to Improve Higher Order Thinking Skills of Fourth Grade Students at Masadian Public Elementary School - Ni Ketut Nurdarmayanti; Hasan Hasan; Nuraedah Nuraedah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study was motivated by the low level of Higher Order Thinking Skills (HOTS) among Grade IV students in IPAS (Integrated Science and Social Studies) learning, particularly in the theme “Caring for the Environment” at SD Negeri Masadian. Conventional teaching methods still dominate, limiting students’ opportunities to think critically and solve problems independently. The purpose of this research was to describe the implementation of an inquiry-based learning model and examine its impact on students’ HOTS. A qualitative descriptive approach was employed, involving 30 students of Grade IV, along with the school principal, classroom teacher, and IPAS subject teacher. Data were collected through observation, interviews, documentation, questionnaires, and HOTS-based tests. The findings showed significant improvements in three core competencies: (1) analytical skills, seen in students’ ability to break down environmental issues and present logical arguments; (2) synthesis skills, reflected in integrating diverse information into data-driven solutions; and (3) evaluative skills, demonstrated by assessing information sources, comparing alternatives, and making evidence-based decisions. In conclusion, the inquiry-based approach effectively enhanced students’ critical, reflective, and integrative thinking, enabling them to connect IPAS concepts with real-life environmental challenges.